Kajian Potensi Ketersedian Air Menggunakan Model Neraca Air Bulanan Thornthwaite-Mather (Studi Kasus : Sub Das Subayang Kampar Kiri Hulu - Cuprtino Tamba; Manyuk Fauzi; Imam Suprayogi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Water quantity is an important factor in evaluating water resources. It must be measured directly, However not all of the watersheds has hydrology station, the quantity or the amount of the water can be measured by modeling. One of the simple models in estimating the potential of water each month is Thornthwaite-mather method. This method is based on water balance. The rain as an interior, the evapotranspiration and the discharge of water as superficial. The characteristics of the soil physically and the occlusionof land area as a processor. The aim of this research is to getan information about the appraising of the availability of the water per month. The result of this research shows that the appraising of the potential of the availability of water assumed that 50% of the surplus of the water will be become runoff. The Runoff computation of the surface will be start as soon as the dry season ending. (S>0)in which at this point, assumption 50% is used from the surplus that will be added to the run-off for the upcoming month in and the Runoffis the amount of the availability of the water in the sub watersheds Subayang of the water in the sub watersheds Subayang.In order to get the good result of the standard comparison.The result of the water measurement is better to be checked again.Keywords: Water potensial estimation, Direct mesurement